HUBUNGAN MOTIVASI BELAJAR TERHADAP SELF DIRECTED LEARNING READINESS (SDLR) PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS ABDURRAB PEKANBARU - Olvaria Misfa; Sandra Putri Yulita; Huda Marlina Wati; Riski Dwi Utami (Collaborative Medical Journal, 2024)
Self directed learning readiness (SDLR) is the readiness of students to learn independently. SDLR implements learning that involves a self-view that focuses on overall independence. In students with low SDLR, it is caused by a lack of motivation in learning in students and ignorance of students in learning independently. The Faculty of Medicine, Abdurrab University is one of the Faculties of Medicine that implements a learning system with the concept of student-centered learning with a problem-based learning approach. The use of PBL with a student-centered learning system at the Faculty of Medicine, Abdurrab University encourages students to have SDLR as a support for the student learning process so that they get maximum results. Based on the preliminary research that has been carried out from the results of the final exam of the module, there are no students who pass the final exam of the module. The purpose of this study is to find out whether there is a relationship between learning motivation and self-directed learning readiness (SDLR) in students of the Faculty of Medicine, Abdurrab University, Pekanbaru. Methods This study uses a type of analytical observational research with a cross sectional method. Sampling technique was carried out by stratified random sampling technique on students of the Faculty of Medicine, Abdurrab University at the academic stage. Data analysis uses the Spearman correlation test. The results of the correlation between learning motivation and self-directed learning readiness (SDLR) in students of the Faculty of Medicine, Abdurrab University (p-value <0.05) with a correlation value of 0.459 with a moderate correlation strength were obtained.